2022
DOI: 10.3389/fendo.2022.1091462
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum NDRG3 and papillary thyroid carcinoma

Abstract: BackgroundIn recent years, papillary thyroid carcinoma is considered to be one of the fastest increaseing cancer. NDRG family member 3 (NDRG3) has been proposed as a molecular marker of tumor, and is expected to be used in clinic.MethodsEnzyme-linked immunosorbent assay was used to detect the serum NDRG3 expression in 81 papillary thyroid carcinoma cases, 75 benign thyroid nodules cases and 77 healthy control cases, respectively. Electrochemiluminescence method was applied to measure the levels of triiodothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The DAZAP1 gene is highly expressed in testis (RPKM 19.6), appendix (RPKM 11.8). A number of publications have shown the involvement of the NDRG3 gene in the development of oncogenesis, and in most cases, increased expression is observed in cancer of various organs [70][71][72][73][74][75][76]. Therefore, it is important to know whether piR-3215034 and piR-6885965 can suppress the expression of the NDRG3 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The DAZAP1 gene is highly expressed in testis (RPKM 19.6), appendix (RPKM 11.8). A number of publications have shown the involvement of the NDRG3 gene in the development of oncogenesis, and in most cases, increased expression is observed in cancer of various organs [70][71][72][73][74][75][76]. Therefore, it is important to know whether piR-3215034 and piR-6885965 can suppress the expression of the NDRG3 gene.…”
Section: Resultsmentioning
confidence: 99%
“…NDRG3 has been implicated in many types of cancer and is a member of the NDRG family. [33][34][35][36] NDRG3 expression was associated with various types of infiltrated immune cells. 36 Shi et al 37 demonstrated that low levels of infiltrating DC cells and neutrophils were associated with high levels of NDRG3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that DNAJA1 expression in clinical tumor tissues was significantly higher than in normal tissues and that high DNAJA1 mRNA expression was associated with low survival in breast cancer. NDRG3 has been implicated in many types of cancer and is a member of the NDRG family 33–36 . NDRG3 expression was associated with various types of infiltrated immune cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections inhibit the activity of ciliated cells and phagocytosis of alveolar macrophages, which in turn causes the invasion of bacteria, including Streptococcus pneumoniae and Klebsiella pneumoniae. 26 Meanwhile, persistent low temperatures may cause the combustion of petroleum products to release more toxic byproducts, such as NO 2. 27 These factors contribute to the frequency of respiratory illnesses under low-temperature conditions.…”
Section: Discussionmentioning
confidence: 99%